The pluses of the Vetus Latina of the Book of Esther - Candido, Dionisio (Journal of septuagint and cognate studies, 2020)
In the text critical research on the book of Esther in recent years the importance of the Vetus Latina has been acknowledged. Looking carefully at its text in comparison with the other ancient texts (the Masoretic Text, Old Greek and Alpha Text), one can notice some significant pluses. Among other things, these reveal the tendency to deepen the psychological description of the characters and to provide a certain narrative coherence. This paper deals with those pluses in order to explicate the knowledge about their literary function and their possible relevance to the textual critical debate concerning the place of Vetus Latina in the history of the textual transmission.